Private Speech Moderates the Effects of Effortful Control on Emotionality. Issue 2 (17th February 2018) - Day, Kimberly L.; Smith, Cynthia L.; Neal, Amy; Dunsmore, Julie C.
ABSTRACT: Research Findings : In addition to being a regulatory strategy, children's private speech may enhance or interfere with their effortful control used to regulate emotion. The goal of the current study was to investigate whether children's private speech during a selective attention task moderated the relations of their effortful control to their anger and sadness. The private speech of 156 preschoolers (age in months: M = 52.10, SD = 9.24, min = 36.20, max = 69.50) was transcribed and coded during a selective attention task. Effortful control was observed and reported by parents. Anger and sadness were reported by parents and observed in a frustration task. Children who used more inaudible muttering had higher levels of sadness. Effortful control interacted with private speech to explain anger. The negative relation of effortful control to anger was significant for children who used low and moderate but not high levels of task-irrelevant private speech. Practice or Policy : The presence of private speech, although it may support regulatory abilities within a task, may be an additional form of evaluation that might help teachers and caregivers decide how best to support children's learning. These findings suggest that private speech can be used as an indicator of how well children use other regulatory abilities, such as effortful control.